Wacana Dinamis Nahdlatul Ulama: Analisis Kritis terhadap Perubahan Sosial: Nahdlatul Ulama's Dynamic Discourse: A Critical Analysis of Social Change - Haeba, Ilham Dwitama; Thoha , Anis Malik; Ahim, Rasinah (University of Darussalam Gontor, Indonesia, 2024)
This research presents critical study of Nahdlatul Ulama’s dynamic discourse on social change. The background of this study is rooted in the significant role of NU in the history of Indonesia, particularly in the realm of cultural and religious ideologies. The research methodology employed encompasses a combination of qualitative approaches and document analysis to attain a comprehensive and profound comprehension, to understand how the NU tradition is integrated into moderate thinking and the extent to which the transformation of such thinking can act as a catalyst for societal progress. The theoretical framework of this research encompasses a profound understanding of the traditional values of NU, the concept of moderation as the cornerstone of thinking, and how thinking evolves in the face of contemporary challenges. The results of the analysis indicate that NU traditions not only persist in everyday life but are also effectively assimilated into the modern context. Moderation, as a pivotal aspect of NU thought, emerges as a crucial component in promoting interreligious dialogue and contributing to political stability. The transformation of NU's thinking is evident in its response to advancements in technology and science. Although NU thinking encounters challenges, particularly in preserving cultural heritage, this study underscores the opportunities for the development of NU thinking in the future. The conclusions of this study offer a critical evaluation of NU's impact on societal change and emphasize the significance of comprehending and permeating traditional values while remaining relevant in the face of evolving times. The implications of this research hold valuable insights for academics, practitioners, and policymakers in supporting the positive development of a society founded on the moderate values of NU.